Factors Predicting Health-Promoting Behaviors among Caregivers of Children under 5 Years during the COVID-19 Pandemic: Cross-Sectional Study in Rural Thailand - Thepsaw, Jintana; Moonpanane, Katemanee; Trakooltorwong, Pimkanabhon; Kodyee, Salisa; Wuttipan, Nathamon; Maneekunwong, Kunnara (Journal of Health Sciences and Wellness, 2024)
The COVID-19 pandemic and associated quarantine measures have had a negative impact on children and caregivers, both mentally and physically. Children who receive inappropriate health-promoting behavior from the caregiver could have health problems. This study aimed to identify factors influencing the health-promoting behaviors (HPBs) of caregivers of children under five years of age while experiencing lockdowns. The cross-sectional study conducted between March and May 2021 had 138 caregivers of children who completed the questionnaires, which captured demographic information, parenting style, social support, self-efficacy, and HPBs. The study used descriptive statistics and multiple linear regression to determine the predicting factors of the HPBs of caregivers. The results showed the mean age of the participants was 34.06 + 8.96 years, more than half were recognized as day laborers (69.6%), and one-third had primary school education (30.4%). The percentage of total variance explained by all study variables (parenting style, social support, and self-efficacy) was 29.8 percent (adjust R2 = .298, F = 20.420, p < .001), and self-efficacy was the best predictor of the HPBs of caregivers (ß = 0.580, p < .001). These findings represent a preliminary stride towards recognizing the factors that influence the development of HPBs among caregivers of children under five years old. In achieving this, there is a need to enhance the caregivers' self-efficacy and direct interventions to counteract the adverse effects on the health of children residing in a rural community during and following the COVID-19 Pandemic.